Cerebral Cavernous Malformations: Review of the Genetic and Protein–Protein Interactions Resulting in Disease Pathogenesis - Baranoski, Jacob F.; Kalani, M. Yashar S.; Przybylowski, Colin J.; Zabramski, Joseph M. (Frontiers in Surgery, 2016)
Mutations in the genes KRIT1, CCM2, and PDCD10 are known to result in the formation of cerebral cavernous malformations (CCMs). CCMs are intracranial lesions comprised of aberrantly enlarged “cavernous” endothelial channels that can result in cerebral hemorrhage, seizures, and neurologic deficits. Although these genes have been known to be associated with CCMs since the 1990s, numerous discoveries have been made that better elucidate how they and their subsequent protein products are involved in CCM pathogenesis. Since our last review of the molecular genetics of CCM pathogenesis in 2012, breakthroughs include a more thorough understanding of the protein structures of the gene products, involvement with integrin proteins and MEKK3 signaling pathways, the importance of CCM2-PDCD10 interactions, and others. In this review, we highlight the advances that further our understanding of the gene to protein to disease relationships of CCMs.